Synergistic Treatment of Alkali Lignin via Fungal Coculture for Biofuel Production: Comparison of Physicochemical Properties and Adsorption of Enzymes Used As Catalysts - Ruhong, Luo; Liao, Qiang; Xia, Ao; Deng, Zhichao; Huang, Yun; Zhu, Xianqing; Zhu, Xun (Frontiers in Energy Research, 2020)
White-rot fungi is capable of producing extracellular enzymes that degrade lignin structure and facilitate biofuel production from lignocellulosic biomass wastes. However, fungal monocultures are constrained by low activities of the lignin-degrading enzyme system, leading to poor treatment efficiency and a long duration, which are not advantageous for large-scale applications. To improve enzyme production and enhance lignin degradation, a novel coculture system was proposed using the white-rot fungi Phanerochaete chrysosporium and Irpex lacteus CD2. The degradation efficiency of the alkali lignin by the fungal coculture was 26.4%, which was higher than that of the fungal monocultures. It was due to the production of lignin degrading enzymes was promoted in the liquid medium. Scanning electron microscopy, Fourier transform infrared, thermogravimetric and mercury porosimeter analyses results revealed that the alkali lignin treated with the fungal coculture had the largest porosity, and the degree of destruction of the alkali lignin structure by the fungal coculture was higher than that of the fungal monocultures. Meanwhile, the nonproductive adsorption of enzymes on alkali lignin was significantly reduced by 61.0% when the biomass was treated with the fungal coculture. As a result, the nonproductive adsorption was remarkably reduced, while it significantly improved the cellulase catalysis efficiency. These results demonstrated the synergistic effects of the fungal coculture for biomass treatment and provided a new approach for increasing lignin degradation while improving enzymatic catalysis and biofuel production through fungal coculture.